Real-world experience with Temozolomide & Sativex in patients with recurrent High Grade Gliomas. (12th October 2019) - Shahabi, Lillie; Le Calvez, Kerlann; Dadhania, Seema; Blake, Catherine; Wang, James; Ingle, Manasi; Anichini, Giulio; Peterson, David; Nandi, Dipankar; Camp, Sophie; Saleem, Waqar; Falconer, Alison; et al.
Abstract: Background: Glioblastoma (GBM) is the most common malignant brain tumour in adults with a median survival from progression of 8 months. A recent phase 1 study of temozolomide (TMZ) and 1:1 CBD:THC (Sativex) offers evidence of efficacy in patients with recurrent GBM (NCT01812603). Methods: All patients receiving TMZ & Sativex (75mg/m 2 daily d1 – 21 q28; Sativex continuously) for relapsed GBM or grade 3 astrocytoma at our centre were identified. Patient, tumor and treatment characteristics were recorded, and response based on sequential MRI scans using modified RANO criteria assessed. Results: 13 patients were treated over 18 months. The median age was 56; 69% were male. All had received initial chemo-radiotherapy (12 patients: 60 or 59.4Gy/30–33#; 1 patient: 45Gy/15#). 6 patients underwent reresection at recurrence. 4 patients were treated at first progression, 7 at second progression, and 2 at third or later progression. The median number of cycles of TMZ and sativex was 2. The combination treatment was tolerated well by all patients treated, with no Grade 3 or 4 toxicities, the only complaints being of discomfort in mouth after spray and 'spaced out feeling'. Patients stopped treatment due to evidence of progressive disease on sequential MRI sign or physical deterioration. Median Overall Survival (OS) from initiation was 5.9 months (177 days); Progression Free Surival (PFS) at 3 months was 50%. Conclusion: These results highlight some discrepancies in OS in comparison to the previous trial (NCT01812603), but our patients were treated at second/ third recurrence. We agree that the combination is well tolerated.